Beltrami-Mitchell’s compatibility equations in the problem of dinamic thermoelasticity. - A. . Bykov; У. . Pautova; E. . Kartashov (Тонкие химические технологии)
The article is delicated to deduction of the generalized equation of dynamic thermoelasticity in thermal stresses.